2001
DOI: 10.1103/physrevb.64.195309
|View full text |Cite
|
Sign up to set email alerts
|

Highly confined excitons in MgS/ZnSe quantum wells grown by molecular beam epitaxy

Abstract: MgS has been grown by molecular beam epitaxy in the zincblende crystal structure on GaAs ͑100͒ substrates using a technique where the sources are Mg and ZnS. Layers up to 134 nm thick have been grown without any degradation in the crystal structure. The lattice constant was found to be 0.5619Ϯ0.0001 nm and Poisson's ratio was estimated to be 0.425. The success of this growth technique has allowed the fabrication of MgS/ZnSe/MgS quantum wells that show sharp photoluminescence and transmission spectra indicating… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
54
1
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 43 publications
(66 citation statements)
references
References 38 publications
10
54
1
1
Order By: Relevance
“…Modelling of the XRD spectra of the multi quantum well samples suggests that the interfaces contain an interfacial region which is at most 0.6 nm wide. Although no thermodynamic calculations have been reported to date for the (Cd,Mg)(S,Se) alloy system, we have suggested that, by analogy with (Zn,Mg)(S,Se), there is a large miscibility gap in this system as well [13]. Comparisons between the deposition of CdSe layers on MgS and ZnSe show that the two systems behave very differently, despite the very similar lattice constants of ZnSe, MgS and the GaAs substrate [23].…”
Section: Properties Of Structures Containing Mgsmentioning
confidence: 71%
See 2 more Smart Citations
“…Modelling of the XRD spectra of the multi quantum well samples suggests that the interfaces contain an interfacial region which is at most 0.6 nm wide. Although no thermodynamic calculations have been reported to date for the (Cd,Mg)(S,Se) alloy system, we have suggested that, by analogy with (Zn,Mg)(S,Se), there is a large miscibility gap in this system as well [13]. Comparisons between the deposition of CdSe layers on MgS and ZnSe show that the two systems behave very differently, despite the very similar lattice constants of ZnSe, MgS and the GaAs substrate [23].…”
Section: Properties Of Structures Containing Mgsmentioning
confidence: 71%
“…While this transition is easy to describe, it is not obvious to see how it actually occurs. We have determined that it is not nucleated within the bulk of the film, but must originate on the surface [12,13]. Its occurrence is preceded by the formation of regular linear features ori-…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…This technique was developed for the growth of ZB magnesium sulphide (MgS) [2] but we have demonstrated that MnS layers of up to 132 nm can be grown in the ZB phase [3]. This is over four times thicker than the samples reported previously grown using conventional MBE [1].…”
mentioning
confidence: 89%
“…In previous studies, we have shown that using ZnS as a sulphur source, both MgS [1] and MnS [2] can be grown epitaxially on GaAs substrates in the metastable zinc blende (ZB) structure. Thicknesses in excess of 130 nm have been produced before the conversion to the stable rocksalt (NaCl) structure.…”
Section: Introductionmentioning
confidence: 99%